High sulfur solubility in subducted sediment melt under both reduced and oxidized conditions: With implications for S recycling in subduction zone settings. (1st July 2021) - Li, Huijuan; Zhang, Lifei; Bao, Xinjian; Wykes, Jeremy L.; Liu, Xi
Highlights: In hydrous rhyolitic melt, S is dissolved as H2 S/HS − (reduced) or SO4 2− (oxidized). H2 S and SO2 dissolution in rhyolitic melt follows the Fincham-Richardson relationship. SCSS in hydrous rhyolitic melt increases with decreasing f O2 . Subducted sediment melts have high SCSS values when FeO contents are low. Abstract: The relative enrichment of sulfur (S) observed in arc magmas when compared to MORB, reflects the addition of slab-derived S to the mantle wedge source region. However, the mechanisms and efficiency of such S recycling remain poorly constrained. In this study, sediment melting experiments have been conducted using a synthetic pelite starting composition containing ∼7 wt% H2 O and ∼1.9 wt% S, at 3 GPa, 1050 °C and variable oxygen fugacity ( f O2 ), to investigate the effect of f O2 on S solubility in sediment melts. To assess temperature and concentration effects, selected experiments were repeated either at lower temperatures of 950 °C and 1000 °C, or with a higher bulk S content of ∼4 wt%. All experiments produced hydrous rhyolitic melts, saturated with either pyrrhotite under reduced conditions or anhydrite under oxidized conditions. For 3 GPa, 1050 °C experiments, the sulfur content at sulfide saturation (SCSS) in melt is found to increase with decreasing f O2, from ∼200 ppm at FMQ-0.5 to ∼1900 ppm at FMQ-7.5. The highest S solubility is achieved at FMQ + 1.6 where melt is saturated with both anhydrite and pyrrhotite. The sulfur content at sulfate saturation (SCAS) decreases from ∼2600 ppm at FMQ + 1.6 to ∼2000 ppm at FMQ + 7. Increasing either bulk S content or temperature produces a positive effect on SCSS and SCAS. Raman spectra of our experimental melts show that S exists as H2 S/HS − under reduced conditions and as SO4 2− under oxidized conditions. The solubility minimum, i.e., the onset of transition from S 2− to S 6+ is estimated to occur at ∼FMQ, with full transition to S 6+ by ∼FMQ + 2. While the SCAS values are in good agreement with previous reports, the distinct increase of SCSS with decreasing f O2 (when f O2  < FMQ) has not been observed in previous slab melting experiments. Furthermore, we report for the first time that dissolution of H2 S and SO2 in hydrous rhyolitic melt follows the Fincham-Richardson relationship; and propose the definition of a hydro-sulfide capacity as C HS  = [HS]*( f O2 / f S2 ) 1/2 ; where [HS] is the concentration of S in melt (in ppm) dissolved as HS − and H2 S. SCSS for H2 S dissolution can therefore be modeled using C HS in an analogous fashion to modeling SCSS for anhydrous melts using the sulfide capacity ( C S 2− ), with the relation ln [ HS ] SCSS = - Δ G Fes - FeO ° / R T + ln C HS - ln a FeO melt + ln a FeS sulfide . As predicted by such a model framework, we indeed observe a linear correlation between logSCSS and log X FeO (the mole fraction of FeO in melt) with a slope close to −1, i.e., SCSS experiences a sharp increase when FeO in melt falls below 1 wt%. Therefore, both our experimental results and model predictions suggest hydrous low-Fe rhyolitic melt produced by sediment melting under reduced conditions has the required S solubility to account for the relative enrichment of S observed in arc magmas.